If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 22y = 40 Solving 15x + 22y = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22y' to each side of the equation. 15x + 22y + -22y = 40 + -22y Combine like terms: 22y + -22y = 0 15x + 0 = 40 + -22y 15x = 40 + -22y Divide each side by '15'. x = 2.666666667 + -1.466666667y Simplifying x = 2.666666667 + -1.466666667y
| 18-8=x/3 | | 7x^(2/3)-13x^(1/3)-2=0 | | 6-18=-4z | | -6(4x-5)+5(5x-3)-6=2-4 | | -3(4x+2)= | | 86-76=39y-44y | | 4w^2+4w+1= | | -4.22-0.807= | | 3x^(1/2)-7x^(1/4)=6 | | -4*10= | | 32x+24y=640 | | 20n+12=16n-16 | | 8x-7=8(x+2) | | 10y-120+3x+45=180 | | 9/5(-10)+32=f | | X+14/13=12/13x | | x+3/12=5/6 | | 9x-(4x-9)=7+4x | | (2x-7)=7 | | 6-8y=5y+19 | | 3t+6t=16-8+28 | | 8(11v)= | | 3^3/2-6=75 | | 40x^2-83x+42=0 | | -25=m-8 | | 3*2-1/5*4+23 | | 2b-5-11b-7= | | 3t+6t=18-8+28 | | 17-1/5(35n+15)=-8n-15 | | ((2*a^-5*b^4*c^3)^-2)/((3*a^3*b^-7*c^3)^2) | | y=3.3x-6.6 | | -3/2+7 |